The Florence Legacy - Snelling, Lauraine (Thorndike, Maine : Center Point Large Print, 2023)
"As the last will of a close friend is read, three women discover that they have inherited a legacy from her: the funds to take a dream trip to Florence, Italy, in her memory. With plenty of hilarious travel mishaps along the way, this book is a story of deep friendship, of making room in our lives to celebrate and remember, of grief, of the realization that friendship keeps the memory alive, and the sweet discovery of unexpected romance."--
Keywords: Female friendship -- Fiction; Reunions -- Fiction; Travel -- Fiction; Grief -- Fiction; Florence (Italy) -- Fiction; Romance fiction; Christian fiction; Large print books